Through-bond interactions in the diradical intermediates formed in the rearrangements of bicyclo(n.m.0)alkatetraenes - Lovitt, Charity Flener; Dong, Hao; Hrovat, David A.; Gleiter, Rolf; Borden, Weston Thatcher (Journal of the American Chemical Society, 2010)
The intermediates and transition structures in the degenerate thermal rearrangements of bicyclo[4.4.0]deca-2,4,7,9-tetraene (1c), bicyclo[5.5.0]dodeca-2,4,8,10-tetraene (11b), and bicyclo[5.4.0]undeca-2,4,8,10-tetraene (14) have been located by (U)B3LYP/6-31G(d) calculations. The singlet−triplet energy differences (ΔEST) in the diradical intermediates (tricyclo[4.4.0.02,7]deca-3,8-dien-5,10-diyl (2c), tricyclo[5.5.0.05,11]dodeca-2,8-dien-4,10-diyl (12b), and tricyclo[5.4.0.05,11]undeca-2,8-dien-4,10-diyl (15)) have been computed, using both UB3LYP and (6/6)CASPT2 calculations. ΔEST in 2c, in which a four-membered ring is anti-bridged by two allylic radicals, is computed to be larger by a factor of 5 than ΔEST in 15, in which the anti-bridged ring is five-membered, and by a factor of 10 than that in 12b, in which the anti-bridged ring is six-membered. The reasons for the much larger interaction between two allylic radicals through the bonds of the four-membered ring in 2c than through the bonds of the five-membered ring in 15 or the six-membered ring in 12b are discussed, and the consequences of the large, through-bond stabilization of the singlet state of 2c are described.
Im Titel steht der Ausdruck "n.m.0" in eckigen Klammern
Gesehen am 19.04.2023